Lecturer’s Motivational Strategies in Teaching English - Indah Rahmalia (Linguistic, English Education and Art (LEEA) Journal, 2019)
This research was aimed to describe the lecturer’s motivational strategies in Teaching English at STKIP Yayasan Abdi Pendidikan Payakumbuh.This research was descriptive research in qualitative method. Participants in this research were three English lecturers who teach in Indonesian Department. Those were chosen by using total sampling. Researcher used observation, recording and field notes as the sources of the data. Checking data trustworthiness had been done by using peer briefing. After doing the research, the result showed that the most motivational strategies used by the lecturers was creating basic motivational conditions. Percentage was 24,65%. concluded that the English lecturer had used some kinds of motivational strategies in teaching English, strategy that used by the lecturers is creating the basic motivational conditions Keywords : motivational strategies, teaching english